A Path From Childhood Sensory Processing Disorder to Anxiety Disorders: The Mediating Role of Emotion Dysregulation and Adult Sensory Processing Disorder Symptoms - McMahon, Kibby; Anand, Deepika; Morris-Jones, Marissa; Rosenthal, M. Zachary (Frontiers in Integrative Neuroscience, 2019)
Although maladaptive sensory processing has been observed among individuals with persistent heightened anxiety, it is unclear if difficulties processing sensory input early in life lead to anxiety disorders in adulthood and what mechanisms would drive this progression. In a transdiagnostic clinical sample of 231 adults characterized by heightened difficulties with emotion regulation, the present study sought to examine whether (a) childhood sensory processing disorder (SPD) symptoms predict an increased probability of an anxiety disorder diagnosis in adulthood and (b) difficulties with emotion regulation and adult SPD symptoms mediate this relationship. Participants were administered the Structured Clinical Interview for Axis-I disorders and self-reported symptoms of SPD experienced in childhood and adulthood. Results from suggested that childhood SPD symptoms were significantly associated with a higher likelihood of a lifetime anxiety disorder diagnosis. Difficulties with emotion regulation fully mediated the relationship between childhood SPD and (a) any anxiety disorder in adulthood and, specifically (b) current generalized anxiety disorder. Further, we found evidence for a candidate model accounting for the relationship among childhood SPD, adulthood SPD, difficulties with emotion regulation, and anxiety disorders in adulthood. Specifically, our data indicated that high symptoms of SPD in childhood may lead to high SPD symptoms in adulthood, which then lead to high emotion dysregulation, ultimately conferring vulnerability for an anxiety disorder diagnosis. Taken together, these findings provide preliminary evidence for how sensory processing impairments in childhood may relate to anxiety through difficulties regulating emotion regulation.